GAYA DAN MAKNA BAHASA TULISAN: KAJIAN DESKRIPTIF CHAT MAHASISWA KEPADA DOSEN (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
Language as a means of communication can be realized in both spoken and written forms. Understanding the meaning and meaning of written language tends to be more complicated than spoken language. The use of language style with a specific purpose also contributes to the delivery of meaning to the interlocutor. This study discusses how language style and meaning in written language play a role in the communication of two parties. So that the written language that is often used in student and lecturer communication via chat becomes an interesting object of study to discuss. This research is a descriptive type with a qualitative approach. Data were collected through documentation and interviews and then analyzed using tabulation techniques based on literature references in the form of journal articles and books for the last fifteen years. The results showed that the language style used by students in chat was the conversational language with periodic, loose, and balanced sentence characteristics. The choice of words is in the form of standard Indonesian vocabulary with the addition of a metaphor which is influenced by the students' own ability in word choice. There is also the use of logat and certain regional languages in line with the familiarity of the lecturers and students concerned. However, in the meaning and understanding of the language, there is no problem because the context of communication between the two parties has never been far from the realm of academics and lectures. So that good communication is built and politeness in speaking and in written language is carried out properly.